Proposing an Analysis System to Monitoring Weightlifting Based on Training (Snatch and Clean and Jerk) - Baghdad Science Journal (مجلة بغداد للعلوم)
Analysis system of sports players is very important for individuals in weightlifting. Assessment of player and strength is important for the performance of weightlifting. This paper proposes an analytical method for weightlifters with check-by-frame video. This analysis system can compute the major steps of seven positions in both snatch and clean and jerk methods in frame-video weightlifting monitoring of movements. Each user can compute the major steps of the seven positions of Hu moments among two frames in the video during training, and the Euclidian distance can be computed for the Hu moment values and lifting moment values in the snatch and clean and jerk methods during training. The outcome of the proposed system shows on efficient, accurate results in monitoring movement analysis in weightlifting for playersduring training in this area.